Parameters in predicting the risk of a prolonged hospital stay in patients with acute exacerbation of chronic obstructive pulmonary disease: a single-centre experience - Aida Mujaković; Belma Paralija; Besim Prnjavorac; Orhan Lepara; Almir Fajkić; Edin Begić; Avdo Kurtović; Midhat Čizmić; Mirad Odobašić (Medicinski glasnik, 2022)
Aim: To identify clinical and laboratory parameters on admission and/or during a hospital stay that would predict prolonged hospital stay in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Methods: A retrospective cross-sectional study was conducted at the Clinic for Pulmonary Diseases and Tuberculosis, Clinical Centre University of Sarajevo for the period 2019-2021 accounting patients admitted due to AECOPD. The need for hospitalization was evaluated according to the current GOLD criteria and certain clinical parameters. Spirometry testing and laboratory analysis were performed for all patients on the day of admission and on the 10th day of hospital stay. Linear regression was used to show the relationship between multiple independent predictor variables and LOS. Results: A total of 50 patients were evaluated during their hospital stay due to AECOPD. Median of LOS was 22.02±1.06, with 90% hospital survival rate. Due to AECOPD the median of LOS in the intensive care unit (ICU) was 4±0.68 days with pH<7.35 in 34% of hospitalized patients. According to spirometry classification on the day of admission, 56% of patients were assigned to group 3 and 16% to group 4 with significant improvement identified on spirometry findings on discharge. Platelets on the day of admission were the only statistically significant positive predictors of the length of hospital stay. Conclusion: Identifying chronic obstructive pulmonary disease patients at risk of frequent exacerbations and appropriate disease management could reduce the disease burden.
Keywords: chronic obstructive pulmonary disease; hospitalization; therapeutics